Determining the binding mechanism of B12N12(Zn) with CH4, CO, CO2, H2O, N2, NH3, NO, NO2, O2, and SO2 gases - Qadir, Karwan Wasman; Mohammadi, Mohsen Doust; Ridha, Noor J.; Abdullah, Hewa Y. (Microporous and mesoporous materials, 2024)
In this study, an exploration of molecular interactions between CH4, CO, CO2, H2O, N2, NH3, NO, NO2, O2, SO2 gas molecules and B12N12(Zn) nanocage is conducted using advanced computational techniques, ωB97XD/Def2tzvp, unraveling fundamental behaviors. Employing global optimization methods and sophisticated tools like the bee colony algorithm in ABCluster software, the research offers insights into energy adsorption processes, confirming molecular stability through DFT calculations. The determination of electrophilicity index values through conceptual DFT analysis sheds light on relative reactivity levels and charge transfer phenomena, emphasizing that in some cases the nanocage's role as a potential electron acceptor. Natural bond analysis of charge transfer direction and valence shell orbital interactions enriches understanding, supported by comprehensive parameter compilation and critical point visualization. Further confirmation of interaction types and strengths through G(r)/V(r) ratios and ELF values enhances comprehension through quantum theory of atoms in molecule analysis. Ultimately, this study contributes significantly to computational chemistry, laying foundations for molecular design and engineering advancements. It sets the stage for future progress in materials science and catalysis, promising innovation in sustainable energy solutions and technological development. [Display omitted] •Molecular interactions explored: CH4, CO, CO2, H2O, N2 with B12N12(Zn) nanocage.•Advanced computational techniques employed: ωB97XD/Def2tzvp.•Insights into energy adsorption processes revealed.•Role as electron acceptor highlighted; charge transfer phenomena analyzed.•Contribution to computational chemistry for molecular design advancements.